Structural Performance Towards Dynamic Earthquake Spectrum Response According to SNI 1726-2012 and SNI 03-1726-2019 (Study Case Hospital Building ini Solo) - Listiana, Icho Dharma Tri; Safarizki, Hendramawat Aski; Marwahyudi, Marwahyudi (ASTONJADRO, 2024)
Tectonic earthquakes are a type of earthquake that can cause significant damage compared to other earthquakes. These tectonic earthquakes often occur in Indonesia, considering that geographically Indonesia is located between active earth plates. So that in earthquake-prone areas it is necessary to plan earthquake-resistant building structures, this is done so that if an earthquake occurs the building does not suffer significant damage. The dynamic response spectrum analysis method produces the base shear and displacement of the structure. The response spectrum is a spectral plot presented as a plot or graph between periods of oscillation of a T-structure, as a function of the maximum response to a certain attenuation rate and seismic load. This study aims to determine a structural response with 3D modeling on a hospital structure in the city of Solo. The study was conducted to determine the effect of the earthquake on the performance of the structure which was analyzed with reference to the regulations of SNI 03-1726-2012 and SNI 03-1726-2019. The modeled building consists of floor slabs, beams and columns, each of which is structurally load refers to the regulations of SNI 1726-2012 and SNI 03-1726-2019 as a comparison which one is more effective. The results obtained from the use of SNI 03-1726-2012 on building structures have better safety performance when compared to analysis with SNI 03-1726-2019.